Basic researchTGF-β regulates invasive behavior of human pancreatic cancer cells by controlling Smad expression - Sawai, Hirozumi; Yasuda, Akira; Ochi, Nobuo; Takahashi, Hiroki; Wakasugi, Takehiro; Azuma, Masaaki; Matsuo, Yoichi; Funahashi, Hitoshi; Sato, Mikinori; Akamo, Yoshimi; Takeyama, Hiromitsu; Manabe, Tadao (Archives of Medical Science, 2007)
Introduction: To investigate the role of Smads in tumor cell activation, we examined changes in Smad expression as well as changes in proliferative and invasive behaviors in transforming growth factor-β (TGF-β) – stimulated pancreatic cancer cells. Material and methods: Expression of TGF-β receptor type I (TβR-I) and type II (TβR-II) was determined using RT-PCR and Western blot analysis in the human pancreatic cancer cell lines BxPC-3, Capan-2, and PANC-1. TGF-β-mediated changes in Smad mRNA expression were examined using quantitative real-time RT-PCR. Proliferation of pancreatic cancer cells was monitored using an MTT assay and cell counting. Invasive behavior was examined using a Matrigel double-chamber assay. Results: TβR-I and TβR-II were expressed in all three cell lines studied here at the mRNA and protein level. Smad2/3 mRNA expression was decreased after TGF-β stimulation in all three cell lines, while Smad4 mRNA expression remained unchanged. Smad6/7 mRNA expression was also attenuated in all three cell lines. TGF-β enhanced the invasive capacity of all three cell lines, but had no effect on the proliferative behavior. Anti-TβR-II antibody inhibited this TGF-β-enhanced invasive potential in pancreatic cancer cells. Conclusions: The Smad pathway, particularly down-regulation of Smad2/3 and Smad6/7, may be responsible for TGF-β-induced invasion of human pancreatic cancer cells.